A Rare Case of Malignant Transformation of Oral Lichen Planus of the Mandible. Issue 12 (December 2016) - Soo, Joanne; Kokosis, George; Ogilvie, Michael; "Sara" Jiang, Xiaoyin; Powers, David B.; Rocke, Daniel J.; Erdmann, Detlev
Abstract : Summary: Oral lichen planus (OLP) is an immune-mediated mucocutaneous disease associated with an increased risk in oral squamous cell carcinoma (OSCC). Nearly all cases of malignant transformation have been reported in patients >40 years old. We report the case of a 37-year-old woman with a 5-year history of erosive OLP who presented with malignant transformation to OSCC. Delineating the margins of the disease was impossible at presentation given her OLP, and she was initially treated with concurrent chemoradiation therapy. She then developed a recurrence of the mandibular alveolar ridge. The patient was successfully treated with a composite resection including a segmental mandibulectomy, buccal mucosa resection, partial glossectomy, and ipsilateral neck dissection. This was reconstructed with a free fibula osteo-septo-cutaneous flap. Mandibular OSCC is a rare complication of OLP with few reports on effective reconstructive interventions. The case represents the youngest reported patient with mandibular OSCC arising in the context of OLP and highlights the utility of the free vascularized fibula graft in the treatment of these patients.